A Critique on the Book Cultural History of the Islamic World (Introduction to the History of Culture and Civilization in the Islamic Period) - Mahdi Ezati; Rohullah Bahrami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The compilation of the cultural history of the Islamic world on the one hand requires mastery of cultural theories and definitions, texts and sources and critique and study of the study history of cultural and civilizational history of the Islamic world in its various cultural and civilizational fields and on the other hand requires a clear definition and provide a clear model for understanding culture. The cultural history of the Islamic world, due to its vastness and diversity, has not yet been seriously considered and all the writings that have allegedly arisen due to the lack of definite definitions and frameworks have addressed only some aspects of this issue and have failed to understand its generality. This article examines the form and content of the book of the cultural history of the Islamic world written by Boroumand Azamipour with a descriptive and analytical method. As a result, the author of the work relies on the common approach in writing such works and adopting a common view of the history of Islamic sciences and civilization due to the lack of a clear definition of the concept of cultural history. Therefore, the cultural history of the Islamic world has been reduced to the history of science and education.